1990
DOI: 10.1139/m90-151
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Bacillus sphaericus mosquito larvicidal proteins

Abstract: Genes for 51.4- and 41.9-kDa insecticidal proteins of Bacillus sphaericus were separately cloned and expressed in Escherichia coli. Both proteins were required for toxicity. Approximately equal numbers of cells containing the 51.4- and 41.9-kDa proteins produced the greatest toxicity; excess 41.9-kDa protein did not affect toxicity, whereas excess 51.4-kDa protein reduced activity. Larvae were killed when 41.9-kDa protein was fed up to 24 h after the 51.4-kDa protein, but not when the order of feeding was reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0
2

Year Published

1992
1992
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 27 publications
5
59
0
2
Order By: Relevance
“…Consistent with previous results (Broadwell et al, 1990a, b; Davidson et al, 1990;Oei et al, 1990), when P51 or P42 were fed alone to larvae they were not toxic, even at a concentration of 250 pg ml-l . A combination of the two proteins was toxic to larvae, confirming that the C. Oei, J .…”
Section: Pur8cation and Cleavage Of The Fusion Proteinssupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with previous results (Broadwell et al, 1990a, b; Davidson et al, 1990;Oei et al, 1990), when P51 or P42 were fed alone to larvae they were not toxic, even at a concentration of 250 pg ml-l . A combination of the two proteins was toxic to larvae, confirming that the C. Oei, J .…”
Section: Pur8cation and Cleavage Of The Fusion Proteinssupporting
confidence: 92%
“…The surviving larvae were counted after Binding of B. sphaericus toxin to mosquito gut 1519 24 h. Previous results showed that maximum toxicity occurred when the 51 and 42 kDa proteins were present in approximately equal concentrations (Broadwell et al, 1990b;Davidson et al, 1990). Based on this observation, the bioassays were designed such that the 51 kDa protein and its deletion derivatives were fed to the larvae in the presence of an equivalent concentration of 42 kDa protein and vice versa.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations